The Use Grammarly App to Support Independent Learning for Writing Practices at Senior High School Students - Dea Lean Arsy Rosyah; Endah Nur Tjendani (STKIP AL HIKMAH SURABAYA, 2025)
This study investigates the effectiveness of the Grammarly app in fostering independent learning for writing practices among senior high school students. The research employs observation and interview data collection methods, with descriptive analysis for observations and thematic coding for interviews. The results demonstrate that Grammarly positively impacts students' independent learning experiences. Initial use of the app yields favorable perceptions, akin to personalized guidance from an English teacher, though concerns about effectiveness emerge as potential barriers to full adoption. The findings align with existing literature on technology-assisted language learning, showing the app's capacity to promote self-directed learning, improve writing skills, and support non-native English speakers in overcoming language barriers. The study underscores the app's potential to enhance language learning outcomes and writing proficiency, echoing prior research.